Menús modernos: comida, familia, salud y género en Bengala colonial - Banerjee, Ishita (El Colegio de México, 2015)
This essay explores a relatively unexamined dimension of the discourse on nation and family in late nineteenth century India—the key emphasis laid on health in the configuration of a new, “modern” family as the basis of a healthy nation—and the importance of the accomplished mistress as the guardian of the family’s health and hygiene. This innovative focus enables a distinct reading of the nationalist discourse and provides elements which can be used to interrogate the concept of gender as necessarily framing relations between the binary of men and women. The importance ascribed to food, in particular healthy food, resulted in the evolution of a “modern” cuisine as men and women participated enthusiastically in the project of producing nutritive and delectable food for a healthy family. At the same time, the distinct ways men and women gave expression to their efforts underscored the discreet notions of authority, education, family, food, health and domestic economy, as well as women’s role that underlay such articulations. By means of a close reading of early cookbooks in Bengali written by women and men, columns on food in journals run by women, and domestic manuals authored by men, the essay contends that health and nutrition enabled men and women to develop a novel discourse on the family, where husband and wife often collaborated to establish their authority vis-à-vis male and female elders in an extended family. This included a move to over-write the extended family with that of a nuclear one. Educated women, in turn, creatively applied notions of love, beauty, nurture and care to legitimize their claims as the true mistress of this new, model family. At the same time, claims over healthy and savory food brought women—in columns of journals—in competition with one another over authenticity and food value, as well as thrift in the execution of their tried and tested recipes. In a similar manner, women authors of cookbooks engaged in rivalry with their male counterparts in order to establish their superior knowledge in matters related to home and family. A careful analysis of such criss-crossing turf battles permits a reading in which gender emerges as a fluid and shifting category that embodies many meanings, and gets restructured in distinct ways. Rather than a simple tale of men versus women engaged in constant combat, on offer are nuanced stories of male and female identities in processes of getting constructed contingently in relation to men and women and women and men, elders and rivals, inside and outside the family. This lays the ground for an interrogation of the limiting, understanding by “default” of “gender” as constitutive of relations only between men and women, and opens up the possibility of rethinking this complex social concept from a distinct location.